The Relationship between Anxiety and Sleep Quality among the Elderly in the Service Area of Puskesmas Haur Gading - Nahdia, Gusti Katrin; Tasalim, Rian (PROMOTOR, 2025)
Good sleep quality is crucial for the physical and mental health of the elderly. However, many elderly individuals experience a decline in sleep quality as they age. According to WHO, 40-70% of the elderly worldwide face sleep issues, such as difficulty falling asleep or frequent awakenings during the night. In Indonesia, this problem is increasing, including in the Haur Gading Health Center area. Anxiety, or excessive worry, is one factor that can worsen the sleep quality of the elderly, especially related to health concerns and dependence on others. This study aims to analyze the relationship between anxiety and sleep quality in the elderly at Haur Gading Health Center. This study used a descriptive correlational quantitative approach with 30 elderly respondents selected using purposive sampling. The instruments used were the Hamilton Anxiety Rating Scale (HARS) and the Pittsburgh Sleep Quality Index (PSQI). Most elderly respondents experienced moderate anxiety (63.3%) and poor sleep quality (60%). Pearson correlation analysis showed a significant relationship between anxiety and sleep quality (p = 0.009). High anxiety contributes to the decline in sleep quality in the elderly. Those experiencing moderate to severe anxiety tend to have worse sleep quality. Addressing anxiety through psychological interventions is expected to improve sleep quality and the well-being of the elderly. There is a significant relationship between anxiety and sleep quality in the elderly. Anxiety management interventions are needed to enhance the quality of life of the elderly.